If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 2y + y + 9x = 0 Reorder the terms: 9x + 3y + 2y + y = 0 Combine like terms: 3y + 2y = 5y 9x + 5y + y = 0 Combine like terms: 5y + y = 6y 9x + 6y = 0 Solving 9x + 6y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6y' to each side of the equation. 9x + 6y + -6y = 0 + -6y Combine like terms: 6y + -6y = 0 9x + 0 = 0 + -6y 9x = 0 + -6y Remove the zero: 9x = -6y Divide each side by '9'. x = -0.6666666667y Simplifying x = -0.6666666667y
| 2n^2+4n-16=0 | | (3x-4)(-7x+4)=0 | | 2/(3-i) | | -4+4x=-8+10 | | -3(s+3)+10=8 | | 3x-18=y | | 3x+11=12-x | | x^2+8.4x-40=0 | | 2x+x+x+y+y= | | x^2-12x+36=13 | | 48-a=4-a+7 | | 2x-14+6x-9+3x+2=180 | | 6x^5-5=43 | | −2/3-7/8w=9/4 | | 2(3x+5)=8x-8 | | 180-55=x | | 57+x+68=180 | | 5r-6=31 | | X^2+ax+100=0 | | 90-34=x | | 4r-6=31 | | -1/6=-8/21y | | 68+48+x=180 | | 8y=6x+60 | | 68+48=180 | | 1-6x+3=16-8x | | 54+3y=x | | (a-0.3)(a-0.5)= | | -6m+18=3m-12m | | 2+4x^2=1 | | (3v-1)(5+v)=0 | | 3x^2+34x=440 |